2001
DOI: 10.1097/00006123-200104000-00015
|View full text |Cite
|
Sign up to set email alerts
|

Stereotactic Navigation for Placement of Pedicle Screws in the Thoracic Spine

Abstract: The low rate of cortical perforations (8.5%) and structurally significant violations (2.2%) in this retrospective series compares favorably with previously published results that used anatomic landmarks and intraoperative fluoroscopy. This study provides further evidence that stereotactic placement of pedicle screws can be performed safely and effectively at all levels of the thoracic spine.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
88
0
2

Year Published

2003
2003
2019
2019

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 119 publications
(93 citation statements)
references
References 14 publications
3
88
0
2
Order By: Relevance
“…At review, 48 papers were excluded as they did not meet the inclusion criteria (Table 1). Thus, 23 publications [5,6,8,9,[12][13][14][15][16][17][18][19][20][21][22][23][24][25][26][27][28][29][30] were analysed in this paper (Table 2; 2 randomised controlled trials, 12 case-control studies and 9 case series). Three studies were in German language and remaining 20 studies were in English.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…At review, 48 papers were excluded as they did not meet the inclusion criteria (Table 1). Thus, 23 publications [5,6,8,9,[12][13][14][15][16][17][18][19][20][21][22][23][24][25][26][27][28][29][30] were analysed in this paper (Table 2; 2 randomised controlled trials, 12 case-control studies and 9 case series). Three studies were in German language and remaining 20 studies were in English.…”
Section: Resultsmentioning
confidence: 99%
“…Computer-assisted navigation allows for simultaneous and multi-planar visualization of spinal anatomy which helps in virtually tracking surgical instruments in relation to displayed anatomy in real time [4]. This has led to its utilisation in pedicle screw placement thus increasing the accuracy of screw positioning in cadavers and patients [5][6][7][8][9].…”
Section: Introductionmentioning
confidence: 99%
“…Kim et al [11] inserted 120 thoracic pedicle screws on five cadavers using a CT-based navigation system and obtained an overall pedicle violation rate of 19.2%, with 65.0% of the perforations being medial. Youkilis et al [27] reported 9.8% cortical violations for 183 imageguided thoracic pedicle screws (T1-T11) placed in 47 patients. In their case series, Amiot et al…”
Section: Discussionmentioning
confidence: 99%
“…With this technique, the in vivo rate of pedicle perforation ranges from 3.0 to 43.0% [2,3,12,20]. Due to this significant variability in accuracy and to the major potential complications of pedicle screw insertion in the thoracic spine, some surgeons use CT-based navigation systems that have proved to be safe and accurate [2,4,11,27]. However, these systems are expensive, require pre-operative CT scans and intra-operative registration, involve a marked learning curve [11] and are not widely available.…”
Section: Introductionmentioning
confidence: 99%
“…All patients underwent a CT scanning of treated level with sagittal and coronal reconstructions in the postoperative period in order to evaluate the position of the pedicle screws according to criteria published by Youkilis et al [11]: (1) ''good position'', the screw does not violate the pedicle cortex or violates it only for 2 mm; (2) ''acceptable position'', the screw violates the pedicle cortex for more than 2 mm, but it provides good bone fixation; (3) ''unacceptable position'', the screw violates the cortex for more than 2 mm, and there are neurological symptoms. CT scan was also performed in order to assess bone fusion rate.…”
Section: Methodsmentioning
confidence: 99%